Impact of mineral fertilizers, growth stimulators, pH regulators, vitamins and pigment supplements on the vitality of entomopathogenic nematodes of Steinernematidae and Heterorhabditidae families - T. M. Kolombar; Y. A. Gugosyan; V. V. Brygadyrenko (Regulatory Mechanisms in Biosystems, 2020)
Parasites of agricultural crops cause significant losses of quality and decrease in the profitability of agricultural production. Complex measures against pests are aimed both at termination of parasites and prevention of repeated infection of plants. One of the most progressive ways of protecting plants against harmful insects is the use of entomopathogenic nematodes. This method is most expedient in the conditions of organic arable farming. The results of our study reveal the impact of the fertilizers in various concentrations on the vitality of nematode larvae (L3) of four species (Steinernema feltiae, S. kraussei, S. carpocapsae and Heterorhabditis bacteriophora) and the possibility of their combined application for the treatment of plants. Mineral fertilizers and stimulators of growth of plants in 1% concentration insignificantly reduced the vitality of larvae, allowing them to be applied at the same time. We determined the tolerance of invasive larvae to pH for S. carpocapsae equaling рН = 0.9–13.4; optimum values of рН without reliable increase in the mortality during 24 h – рН = 1.3–12.8. Increase in the vitality of larvae (L3) of entomopathogenic nematodes was studied. The survivability of the cultures of larvae increased during the use of solutions of vitamins С, В1, В6, В12. We determined the influence of 21 pigment colourings on larvae (L3), the lowest effect on the vitality of nematode larvae was exerted by pigment bases Abrikos (7.0–10.8% mortality during 24 h), Zolotoi Pesok (6.0–11.8%), Pudra Ananasa (7.7–13.4%), and complex DMAE (7.6–17.4%). The results we obtained allow development of recommendations for agriculturalists for combined use of entomopathogenic nematodes with various substances and also improving the vitality of invasive nematodes.